Challenges of doing business in Africa: A systematic review - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
This paper provides a systematic review of challenges to doing business in Africa. It complements the extant literature by answering two critical questions: what are the linkages between the ease of doing business and economic development; and what are the challeng es to doing business in Africa? In providing answers to the se questions, the nexus between the ease of doing business and economic development is discussed in six main strands, namely: wealth creation and sharing; opportunities of employment; balanced regional and economic development; Gross Domestic Product (GDP) and GDP per capita; standards of living and exports. Moreover, challenges to doingbusiness are articulated along the following lines: (i) issues related to the cost of starting a business and doing business; (ii) shortage of energy and electricity; (iii) lack of access to finance; and (v) high taxes and low cross-border trade.
Keywords: L59; O10; O30; O20; O55; 330; Business; Development; Africa